Kaempferol increases apoptosis in human acute promyelocytic leukemia cells and inhibits multidrug resistance genes. Issue 2 (20th October 2017) - Moradzadeh, Maliheh; Tabarraei, Alijan; Sadeghnia, Hamid Reza; Ghorbani, Ahmad; Mohamadkhani, Ashraf; Erfanian, Saiedeh; Sahebkar, Amirhossein
Abstract: Acute promyelocytic leukemia (APL) is one of the most life‐threatening hematological malignancies. Defects in the cell growth and apoptotic pathways are responsible for both disease pathogenesis and treatment resistance. Therefore, pro‐apoptotic agents are potential candidates for APL treatment. Kaempferol is a flavonoid with antioxidant and anti‐tumor properties. This study was designed to investigate the cytotoxic, pro‐apoptotic, and differentiation‐inducing effects of kaempferol on HL‐60 and NB4 leukemia cells. Resazurin assay was used to determine cell viability following treatment with kaempferol (12.5‐100 μM) and all‐ trans retinoic acid (ATRA; 10 μM; used as a positive control). Apoptosis and differentiation were also detected using propidium iodide and NBT staining techniques, respectively. Furthermore, the expression levels of genes involved in apoptosis (PI3 K, AKT, BCL2, BAX, p53, p21, PTEN, CASP3, CASP8, and CASP9), differentiation (PML‐RAR and HDAC1), and multi‐drug resistance (ABCB1 and ABCC1) were determined using quantitative real‐time PCR. The protein expressions of Bax/Bcl2 and casp3 were confirmed using Western blot. The results showed that kaempferol decreased cell viability and increased subG1 population in the tested leukemic cells. This effect was associated with decreased expression of Akt, BCL2, ABCB1, and ABCC1 genes, while the expression of CASP3 and BAX/BCL‐2 ratio were significantly increased at both gene and protein levels. Kaempferol promoted apoptosis and inhibited multidrug resistance in a concentration‐dependent manner, without any differential effect on leukemic cells. In conclusion, this study suggested that kaempferol may be utilized as an appropriate alternative for ATRA in APL patients. Abstract : This study investigates the potential therpaeutic effects of kaempferol in acute promyelocytic leukemia.